2019
DOI: 10.1021/acs.macromol.9b00635
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromic Polydiacetylene Nanotube from Amphiphilic Macrocyclic Diacetylene in Aqueous Solution

Abstract: Creation of tubular structures through the self-assembly of macrocyclic molecules has gained great attention in the chemical, biochemical, and material sciences. Through a designed introduction of two octaethylene oxide and two diacetylene moieties, we prepared a macrocycle MCDA–BisOEG, which is water-soluble and photopolymerizable and displays a lower critical solution temperature (LCST) behavior. The hydrodynamic diameter of MCDA–BisOEG, measured by dynamic light scattering method, was ca. 6.5 nm at 25 °C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Copyright 2007, Royal Society of Chemistry. Nsubuga et al, 2018;Stauber et al, 2018;Takeuchi et al, 2018;Heo et al, 2019;Jung and Park, 2019;Kim and Lee, 2019;Oh et al, 2019;Romero-Ben et al, 2019;Wang et al, 2019a;Zhang et al, 2019a;Adhikary et al, 2020;Fang et al, 2020;Hao and Zhu, 2020;Li et al, 2020;Tian et al, 2020). Our research group has also carried out some related work in this field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2007, Royal Society of Chemistry. Nsubuga et al, 2018;Stauber et al, 2018;Takeuchi et al, 2018;Heo et al, 2019;Jung and Park, 2019;Kim and Lee, 2019;Oh et al, 2019;Romero-Ben et al, 2019;Wang et al, 2019a;Zhang et al, 2019a;Adhikary et al, 2020;Fang et al, 2020;Hao and Zhu, 2020;Li et al, 2020;Tian et al, 2020). Our research group has also carried out some related work in this field.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the preparation methods for PDA have been greatly advanced. PDA structures have been enriched from traditional films, micelles and vesicles to 3D-PDA structures, porous structures, hydrogels, macrocyclic structures, and single-layer nanosheets (Bang et al, 2016;Chae et al, 2016;Krishnan et al, 2016;Okaniwa et al, 2016;Jordan et al, 2017;Li et al, 2017a;Romera et al, 2017;Jeong et al, 2018;Takeuchi et al, 2018;Terada et al, 2018;Heo et al, 2019;Hu et al, 2019;Seo et al, 2019;Shin et al, 2020). Great progresses have also been made in the preparation of reversible and chiral PDA (Chen et al, 2016;He et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of PDAs imparts additional chromogenic and conductive properties to the tubular polymers. 30 …”
Section: Tubular Polymersmentioning
confidence: 99%
“…Interestingly, self-assemblies of macrocycles containing diacetylene moieties should have columnar structures, which upon polymerization would generate PDAs having rigid, carbon nanotube (CNT)-like structures. [16][17][18][19][20][21][22][23] In an effort to further explore this fascinating feature of PDAs, we designed and synthesized several functional macrocyclic diacetylenes (MCDAs) and demonstrated that they undergo columnar packing and UV-induced polymerization to produce tubular PDAs. [20][21][22][23] Thus far, studies carried out in this area have only focused on PDA nanotubes that are generated from assemblies of single MCDA components.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] In an effort to further explore this fascinating feature of PDAs, we designed and synthesized several functional macrocyclic diacetylenes (MCDAs) and demonstrated that they undergo columnar packing and UV-induced polymerization to produce tubular PDAs. [20][21][22][23] Thus far, studies carried out in this area have only focused on PDA nanotubes that are generated from assemblies of single MCDA components. Our thoughts about the design of new PDA based functional materials led us to speculate that a substance containing multiple MCDA moieties would be able to form a self-assembled structure and undergo polymerization to generate a multi-tubular PDA.…”
Section: Introductionmentioning
confidence: 99%